PENINGKATAN LITERASI KESEHATAN MASYARAKAT BAGI SISWA MADRASAH DI MTS NEGERI 4 KOTA JAMBI - Amir, Andy; Noerjoedianto, Dwi; Puspita Sari; Mekarisce, Arnild Augina; Herwansyah Herwansyah (Universitas Jambi, 2024)
The development of health literacy among madrasah students plays a crucial role in shaping their thought patterns and behaviors from an early age. As teenagers, these students are at a pivotal stage of development where the knowledge and habits they acquire will significantly impact their future health. Strong health literacy enables students to comprehend health information accurately, make informed decisions regarding their health, and adopt a healthy lifestyle in their daily lives. To enhance the understanding of madrasah students at MTsN 4 Municipality of Jambi, a group of lecturers and students from the Public Health Science Study Program at the Faculty of Medicine and Health Sciences, Universitas Jambi, conducted community service activities. These activities involved delivering lectures and engaging in interactive discussions to help participants grasp the fundamental concepts of public health, with a focus on adolescent health components. The objective of this community service endeavor is to raise public health literacy among madrasah students and to encourage the school's ongoing commitment to providing sustainable and pertinent health education for its students.